2008
DOI: 10.1002/asjc.34
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐sensor track‐to‐track fusion via linear minimum variance sense estimators

Abstract: An integrated approach that consists of sensor-based filtering algorithms, local processors, and a global processor is employed to describe the distributed fusion problem when several sensors execute surveillance over a certain area. For the sensor tracking systems, each filtering algorithm utilized in the reference Cartesian coordinate system is presented for target tracking, with the radar measuring range, bearing, and elevation angle in the spherical coordinate system (SCS). For the local processors, each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Performance of various track-to-track fusion algorithms from aspects of fusion accuracy, feedback and process noises are treated in [263]. Perform track fusion optimally for a multiple-sensor system with a specific processing architecture is treated in [295]. Other work cited in Table 2.11 are [338], [15,22,23,24], [16], [17], [19], [21], [20], [71], [72], [73]- [74], [75]- [76], [77], [78]- [79], [124], [126], [260], [261,262], [264,265], [266], [296], [303], [305] and [306].…”
Section: Msdf Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance of various track-to-track fusion algorithms from aspects of fusion accuracy, feedback and process noises are treated in [263]. Perform track fusion optimally for a multiple-sensor system with a specific processing architecture is treated in [295]. Other work cited in Table 2.11 are [338], [15,22,23,24], [16], [17], [19], [21], [20], [71], [72], [73]- [74], [75]- [76], [77], [78]- [79], [124], [126], [260], [261,262], [264,265], [266], [296], [303], [305] and [306].…”
Section: Msdf Systemsmentioning
confidence: 99%
“…Other work cited in Table 2.11 are [338], [15,22,23,24], [16], [17], [19], [21], [20], [71], [72], [73]- [74], [75]- [76], [77], [78]- [79], [124], [126], [260], [261,262], [264,265], [266], [296], [303], [305] and [306]. [266] • Perform track fusion optimally for a multiple-sensor system with a specific processing architecture [295] • Track-to-track fusion for multi-sensor data fusion [296] • Common process noise on the two-sensor fused-track covariance [303] • Track association and track fusion with non-deterministic target dynamics [305] • Comparison of two-sensor tracking methods based on state vector fusion and measurement fusion [306] 2.9. DC-BASED ESTIMATION…”
Section: Msdf Systemsmentioning
confidence: 99%
“…Moreover, Chang et al. compared the performance of the algorithms described in [5], which was shown that IMF is optimal in the Minimum Mean Square Error (MMSE) sense and WCF method is only optimal in the Maximum Likelihood (ML) sense. Further more, Fong [7] demonstrated that IMF has better numerical robustness than WCF method by examining the case of using the mismatched common process noise.…”
Section: Introductionmentioning
confidence: 98%
“…Estimation fusion methods for solving the track-to-track fusion problem have been widely studied over three decades [1]- [9]. Currently, there are two typical state-vector fusion approaches: Weighted Covariance Fusion (WCF) [4], [5] and Information Matrix Filter (IMF) [6]. The IMF is information de-correlation method which was derived by using the information type of Kalman filter (KF).…”
Section: Introductionmentioning
confidence: 99%
“…In [9] a probabilistic domain search and path planning problem is proposed for multiple uninhabited aerial vehicles (UAVs) under global communications. In [11] a distributed fusion scheme is proposed for multi-sensor surveillance. In [11] a distributed fusion scheme is proposed for multi-sensor surveillance.…”
Section: Introductionmentioning
confidence: 99%